EXAMINING ACCOUNTING STUDENTS’ UNDERSTANDING OF GENERAL KNOWLEDGE OF THE STATEMENT OF FINANCIAL ACCOUNTING STANDARDS (PSAK) 210 - Rosa Nikmatul Fajri; Nabila Yoshi Prasetyaningtyas (Politeknik Negeri Ambon, 2026)
Introduction: This study has a long-term objective of identifying and assessing the level of understanding achieved by students after reading PSAK, particularly the general knowledge contained in PSAK 210. The specific objectives of this research are (1) to inform the formulators and developers of PSAK 210 so that they can take into account the readers’ level of understanding when formulating future PSAKs, and (2) to encourage improvements in language structure to ensure clarity and readability.Methods: This study employs a quantitative approach to numerically measure the level of understanding and to provide appropriate solutions aimed at achieving a deeper understanding of the general principles in PSAK 210. To support this approach, two methods were used: (1) distributing questionnaires both offline and online and (2) conducting in-depth interviews. Results: The results of the analysis show that accounting students in the Yogyakarta region fall into several. Level of Understanding categories from the Understanding Index (tables 2 and 3). And then, the level of understanding from data analysis is the “highly understood” category scoring 85,7%, the “not understood” category scoring 5,7%, and the “understood” category scoring 8,6%. Keywords: Accounting, General Knowledge, PSAK 210